Mesenchymal stem cells therapy for acute kidney injury: A systematic review with meta-analysis based on rat model - Pingping Wanyan; Xin Wang; Xin Wang; Nenglian Li; Yong Huang; Yali She; Li Zhang (Frontiers Media S.A., 2023)
Objective: To systematically evaluate the efficacy of mesenchymal stem cells (MSCs) for acute kidney injury (AKI) in preclinical studies and to explore the optimal transplantation strategy of MSCs by network meta-analysis with the aim of improving the efficacy of stem cell therapy.Methods: Computer searches of PubMed, Web of Science, Cochrane, Embase, CNKI, Wanfang, VIP, and CBM databases were conducted until 17 August 2022. Literature screening, data extraction and quality evaluation were performed independently by two researchers.Results and Discussion: A total of 50 randomized controlled animal studies were included. The results of traditional meta-analysis showed that MSCs could significantly improve the renal function and injured renal tissue of AKI rats in different subgroups. The results of network meta-analysis showed that although there was no significant difference in the therapeutic effect between different transplant routes and doses of MSCs, the results of surface under the cumulative ranking probability curve (SUCRA) showed that the therapeutic effect of intravenous transplantation of MSCs was better than that of arterial and intrarenal transplantation, and the therapeutic effect of high dose (>1×106) was better than that of low dose (≤1×106). However, the current preclinical studies have limitations in experimental design, measurement and reporting of results, and more high-quality studies, especially direct comparative evidence, are needed in the future to further confirm the best transplantation strategy of MSCs in AKI.Systematic Review Registration: identifier https://CRD42022361199, https://www.crd.york.ac.uk/prospero.